The Asian Pohlia trematodontea, is a new synonym of Pohlia elongata (Bryophyta, Bryales) - Suarez, Guillermo Martin (2014)
Pohlia trematodontea was first described by C. Müller (1853) as Bryum trematodonteum based on material collected in India, and moved to Webera by A. Jaeger (1875). Crosby et al. (1999), considered the species as insufficiently know. During a visit to the Natural History Museum of London in England (BM), we were able to locate the type material, which consists of contorted leaves when dry and a long capsule (about 5 mm), with a distinct neck (2,6 mm long). The plants of P. trematodontea exhibit thick-walled leaf cells, paroicous sexual condition and endostome teeth yellow, none or narrowly perforate. Our observations confirm that P. trematodontea is indistinguishable from P. elongata, a species widely distributed in temperate, tropical and subtropical regions of the world (Suárez & Schiavone, 2011). Thus, we here propose it as new synonym.